Strategi Pengembangan Perpustakaan di Indonesia - Widanarta, Dian; Latuheru, Grace Wilhelmina; Musangadah, Nur; Widayanti, Ratna Galih; Sukarni, Sukarni (Universitas Negeri Padang, 2022)
The National Library of Indonesia has made a revolution in library development, but not all types of libraries in Indonesia have followed suit. Until now, the results of library development both in terms of quality and quantity have not been optimal. This can be seen in the gap between the number of accredited and unaccredited libraries. The purpose of this study was determine the strategy of the National Library of Indonesia in fostering and developing public libraries, special libraries, school libraries and university libraries in Indonesia. This research method uses qualitative research with a descriptive approach. Data collection techniques using interviews, observation, and literature study. This study examines the strategy of library development in Indonesia is presented in the form of a description or narrative. The development function of the National Library of Indonesia by the work unit of the Public and Special Library Development Center (PPPUK) and the School and College Library Development Center (P3SMPT) with programs are in accordance with their duties and functions as regulators, motivators, and evaluators